Asistensi Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Keterampilan Berfikir Kritis Siswa di SMK Hayatul Islam - Kusno Setiadi; Finti A. Palumbung; Muhamad Rajab; Diyah Fadhilah Zahabiyah; Sofiana Nur Hamidah; Sucilawati Djaniwa; Abdul Majid Jauhari (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
In the midst of the digital era filled with various information, the ability to sort and understand accurate information is very necessary so that students can better understand Islamic teachings. The service of Islamic Religious Education (PAI) learning assistance by improving students' critical thinking skills aims to explore effective learning methods in PAI subjects in order to improve the critical thinking skills of grade XI students at SMK Hayatul Islam. This study applies the assistance method, which includes the stages of observation and coordination, implementation, and evaluation and reflection. Based on the results of the service, it shows that the use of discussion-based methods, problem solving, and analysis of religious texts helps hone students' critical thinking skills. They become more active in conveying ideas and are able to connect religious concepts with everyday life. However, there are several obstacles found, such as students' difficulty in constructing logical arguments and time constraints in the learning process. Therefore, more intensive assistance from teachers and the application of more varied methods are needed so that PAI learning is more effective in developing students' critical thinking patterns.